SCREEN PRINTING TRAINING TO IMPROVE THE SKILLS OF KARANG TARUNA - Muhamad Abdul Rozak; Ibnu Firmansyah; Muhammad Tafri (Khidmatan, 2022)
The Merriam-Webster Dictionary defines skill as the ability to do something that comes from training, experience, and practice. Skill is something that requires basic training and abilities that everyone has in order to produce something more valuable quickly. Skill is a term that includes knowledge, competence, and the ability to perform operational tasks. Skills can be developed through life and work experience or learned through training. Therefore, to improve skills, screen printing training is carried out. Screen printing is a technique to ink with a specific process on fabric materials in various shapes, images, and colors. The ability to print images in fabrics and t-shirts has prospects as an effort to improve creative skills and create independent job opportunities for young people. The aim is to introduce screen printing to the youth groups of Babadan 1 hamlet and provide a deeper understanding to youth groups about the potential to develop the economy through screen printing training. Through this training, the youth are expected to be able to bring about changes in the economy. Babadan 1 hamlet has the potential to have new skills and create new livelihood opportunities. So far, most of the livelihoods of Babadan 1 hamlet are farmers. The training results show an increase in skills and the interest of the youth to open up opportunities for screen printing entrepreneurs as a free time filler during the gap period after the planting season is over.